Cross-cultural adaptation and validation of the Chinese version of the taste and smell survey for cancer patients - Haixin Liang; Qing Yang; Li Yin; Huarong Pang; Enmei Jiu; Bin Li; Lei Qin (BMC Cancer)
Abstract Purpose To translate and culturally adapt the Taste and Smell Survey (TSS) in Chinese for cancer patients and assess its reliability and validity, and to provide a reference for clinical professionals to evaluate taste and smell alterations (TSAs) in cancer patients. Methods With authorization from the original authors, the survey was translated and back-translated following the standard procedure to generate the Chinese version of the TSS. 271 patients were enrolled from a tertiary hospital in China under treatment between January 2023 and February 2024 using a convenience sampling method for reliability and validity testing of the translated scale. Results The overall Cronbach’s α for the Chinese version of the TSS was 0.872. Cronbach’s α for individual items ranged from 0.844 to 0.897. Content Validity Indices (I-CVI) for individual items ranged from 0.833 to 1.000, and the Average Scale-level Content Validity Index (S-CVI/Ave) was 0.972. All indices calculated in the Confirmatory Factor Analysis (CFA) were presented as follows: χ²/df = 3.446, the Goodness-of-fit Index (GFI) = 0.902, the Comparative Fit Index (CFI) = 0.946, the Incremental Fit Index (IFI) = 0.946, the Tucker‒Lewis Index (TLI) = 0.930, the Root Mean Square Residual (RMR) = 0.054, and the Root Mean Square Error of Approximation (RMSEA) = 0.095. All of the above results indicated good validity and reliability of the Chinese version of the TSS. Conclusion The study has confirmed that the Chinese version of the TSS is a concise and effective tool that is easy to administer and demonstrates strong scientific quality, reliability, validity, and feasibility. It is expected to help clinical professionals provide evidence-based interventions related to TSAs in cancer patients undergoing treatments in the Chinese cultural context.